(untitled) (Economic and Political Thought, 2015)
Successive elections to the European Parliament, one of the most important institutions of the European Union, took place in May 2014. Polish citizens took part in the election for the third time. It coincided with the tenth anniversary of Poland’s accession to the European Union. Thus, it is a good time to sum up the effects of our presence in the group of integrated states as well as try to analyse problems and changes that took place in the European Union in the past decade. This is the aim of the article. Moreover, it shows the position and role of the European Parliament in the European Union as well as its powers, which increased when the Treaty of Lisbon entered into force on 1 December 2009. The article also presents the European Union after the elections to the European Parliament in May 2014 and its prospects, which are not so obvious nowadays. As the author writes, various serious threats and black clouds are gathering above the European Union.